Islamic Republic of Mauritania : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note provides World Bank and IMF staff analysis, and advices on key priorities to be strengthened during the implementation of the second Poverty Reduction Strategy Paper (PRSP-2) in Mauritania. The PRSP-2 conveys an ambitious poverty reduction strategy based on a set of sound macroeconomic, structural, and sectoral policies to be implemented by 2015. The achievement of the PRSP-2 objectives will be difficult and will require a better prioritization in the context of absorptive capacity constraints and increasing and highly volatile public resources.